Sedentary Time and Physical Activity Across Occupational Classifications. Issue 3 (March 2020) - Quinn, Tyler D.; Pettee Gabriel, Kelley; Siddique, Juned; Aaby, David; Whitaker, Kara M.; Lane-Cordova, Abbi; Sidney, Stephen; Sternfield, Barbara; Barone Gibbs, Bethany
Purpose: To examine differences in activity patterns across employment and occupational classifications. Design: Cross-sectional. Setting: A 2005-2006 Coronary Artery Risk Development in Young Adults (CARDIA) study. Sample: Participants with valid accelerometry data (n = 2068). Measures: Uniaxial accelerometry data (ActiGraph 7164), accumulated during waking hours, were summarized as mean activity counts (counts/min) and time spent (min/d) in long-bout sedentary (≥30 minutes, SED≥30 ), short-bout sedentary (<30 minutes, SED<30 ), light physical activity (LPA), short-bout moderate-to-vigorous physical activity (<10 minutes, MVPA<10 ), and long-bout MVPA (≥10 minutes, MVPA≥10 ) using Freedson cut-points. Employment status was self-reported as full time, part time, unemployed, keeping house, or raising children. Self-reported job duties were categorized into 23 major groups using the 2010 Standard Occupational Classification. Analysis: Omnibus differences were analyzed using adjusted analysis of covariance and repeated after stratification by race (black/white) and sex (female/male). Results: SED≥30, SED<30, LPA, and MVPA<10 differed significantly by employment and occupational categories ( P ≤ .05), while MVPA≥10 did not ( P ≥ .50). SED≥30, SED<30, and LPA differed by occupational classification in men, women, blacks, and whites ( P < .05). Mean activity counts, MVPA<10, and MVPA≥10 were significantly different across occupational classifications in whites ( P ≤ .05), but not in blacks ( P > .05). Significant differences in mean activity counts and MVPA<10 across occupational classifications were found in males ( P ≤ .001), but not in females ( P > .05). Conclusion: Time within activity intensity categories differs across employment and occupational classifications and by race and sex.